Principles of addiction. - Miller, Peter M. (Peter Michael), 1942- (Comprehensive addictive behaviors and disorders, 2013)
This volume provides an understanding of the definitional and diagnostic differences between use, abuse, and disorder. It describes the characteristics of these syndromes and various etiological models.